An automated microfluidic system with one-dimensional beads array for multiplexed torch detection at point-of-care testing. - Li, Hao; Yu, Shengda; Wang, Dong; Huang, Xinying; Fu, Qiang; Xu, Donglin; Zhang, Lulu; Qian, Shizhi; Qiu, Xianbo (Biomedical Microdevices, 2022)
An automated microfluidic system with functionalized beads has been developed for multiplexed TORCH detection at point-of-care testing. A concise microfluidic chip consisting of a one-dimensional beads array is developed to simultaneously detect TOX, RUB, CMV, HSV-I and HSV-II respectively with five functionalized beads. A compact liquid handling module has been developed to automate the sandwiched chemiluminescence immunoassay within the one-dimensional beads array of the microfluidic chip. A precise ram pump is adopted to not only add reagent into the microfluidic chip from outside, but also facilitate elaborate fluid control inside the microfluidic chip for improved performance. A large-size waste chamber with a liquid-absorbing sponge holds the waste reagent within the microfluidic chip to prevent backflow. The one-dimensional beads array is heated from double-sides at 37 ℃ for sensitive detection with reduced time. A sensitive CMOS camera is adopted to take chemiluminescence image from the one-dimensional beads array, and a custom processing algorithm is adopted to analyze the image. For each serum sample, five different infections can be simultaneously detected with the automated microfluidic system. Experimental results show that efficient, sensitive, and accurate multiplexed TORCH detection can be conveniently achieved with the integrated microfluidic system.